CONCEPTUALLY-THEORETICAL JUSTIFICATION AND UPDATING OF THE PREVENTIVE APPROACH IN THE IMPLEMENTATION OF A PHARMACIST'S INFORMATION CONSULTANCY SERVICES IN THE PUBLIC HEALTH SYSTEM - I. A. Kirshchina; A. V. Soloninina; V. N. Michailova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
Public health protection is the most important law of the development of a civilized society. As participants in the health care system, pharmaceutical specialists must take upon themselves certain preventive tasks aimed at strengthening and maintaining the health of the population.The aim of the work was to substantiate and develop a methodology for implementing the professional role of pharmaceutical specialists in public health protection.Materials and methods. The search for information was carried out using the methods of address, thematic and factual search in the Scopus, The Cochrane Library, Pubmed, eLibrary databases. The analyzed body of information included systematic reviews, retrospective and randomized studies, and other applied developments on the topic of publication. The depth of the bibliographic search for scientific publications is about 20 years (2000-2019). The following keywords were used for the search: "a pharmacist in health protection", "prevention of adverse drug reactions", "functions of a pharmacist", "pharmaceutical care", "sanitary competence", "a pharmacist's role in the prevention of diseases", "pharmacy services", "patient compliance", "collaboration in health care", etc.Results. On the basis of the analysis, the demand for pharmacists in the health protection activities has been substantiated, the scientific and applied methodology of using pharmaceutical knowledge in the protection of public health has been updated and the necessary professional competencies (PC) of a pharmacist have been proposed for their implementation. The relevance of the preventive approach in the implementation of information and consultancy activities of a pharmacist has been substantiated, the essence of which is to prevent undesirable events associated with the use of medicinal preparations (MPs) and preventive health care in the society. The proposed methodology is based on the concept of "a pharmaceutical vigilance", the practical implementation of which is proposed in the publication. The need for pharmacists to perform certain professional functions aimed at preserving and strengthening the health of the population has been updated, the functions have been proposed and the list of possible pharmaceutical services for the practical implementation of the proposed functions in the health care system has been provided.Conclusion. The following pharmaceutical services have been identified as relevant: pharmaceutical enlightenment of the population, patient-oriented pharmaceutical counseling and patronage of patients, pharmaceutical informing of medical specialists about drugs and social prevention of the problems affecting the public health. The definitions of pharmaceutical services have been specified, the methodology for providing the services has been substantiated, the efficiency of their provision has been updated and the professional competencies of pharmacists for their implementation in practical healthcare have been formed.